THE MAIN DIFFICULTIES IN LEARNING PROBABILITY THEORY - Mammadova, Jabarud; Aliyeva, Turkan; Hasanova, Matanat (SWorldJournal, 2024)
Elementary probability theory is a field of mathematics that studies random events and patterns associated with their occurrence. The basic concepts of probability theory, such as a random event, probability, combinations and statistics, lay the foundatio